Investigation of the Lipid-Lowering Mechanisms and Active Ingredients of Danhe Granule on Hyperlipidemia Based on Systems Pharmacology - Chen, Kuikui; Ma, Zhaochen; Yan, Xiaoning; Liu, Jie; Xu, Wenjuan; Li, Yueting; Dai, Yihang; Zhang, Yinhuan; Xiao, Hongbin (Frontiers in Pharmacology, 2020)
Objective: Investigate the active ingredients and underlying hypolipidemic mechanisms of Danhe Granule (DHG). Methods: The lipid-lowering effect of DHG was evaluated in hyperlipidemic hamster induced by high-fat diet. The ingredients absorbed into the blood after oral administration of DHG in hamsters were identified by UHPLC-Q-TOF/MS. A systems pharmacology approach which incorporated target prediction and network construction, GO enrichment and pathway analysis was performed to predict the active compounds and map the compound-target-disease network. RT-PCR and Western blot were utilized to analyze the expression levels of predicted targets. Results: DHG remarkably lowered the levels of serum TC, TG, LDL-c and arteriosclerosis index (AI), at the same time, elevated the levels of serum HDL-c and HDL-C/TC ratio in high-fat diet hamster. Sixteen ingredients absorbed into blood after oral administration of DHG were identified as the possible components interacted with targets. Moreover, 65 potential targets were predicted after targets intersection and compounds-targets-disease network mapping. Then, compounds-targets-pathways network mapping revealed that emodin and naringenin, etc. 6 active compounds could interact with 10 targets such as SREBP-1c, SREBP-2, PPARα, and so on, regulating 3 lipid metabolism-related pathways including SREBP control of lipid synthesis pathway, PPAR signaling pathway and nuclear receptors in lipid metabolism and toxicity pathway, further affecting lipid metabolism process including fatty acid biosynthesis, LDLR-mediated cholesterol uptake, bile acid biosynthesis and cholesterol efflux. Experimental results indicated that DHG significantly increased SREBP-2, LDLR, PPARα, LXRα, CYP7A1 and ABCA1 mRNA and protein expressions while decreasing SREBP-1c and FAS mRNA and protein expressions. Conclusion: DHG possessed a good hypolipidemic effect that maybe through affecting the expressions of SREBP-1c, FAS, SREBP-2, LDLR, PPARα, LXRα, CYP7A1 and ABCA1, involving in fatty acid synthesis, LDLR-mediated cholesterol uptake, bile acid biosynthesis and cholesterol efflux. This study further provided experimental evidence about its practical application for treating hyperlipidemia and its complications.